Considering FERPA requirements for library patron databases within a consortial environment. Issue 1 (2nd January 2016) - Oliver, Astrid; Prosser, Eric; Chittenden, Lloyd
Abstract: This case study examines patron record privacy and the Family Educational Rights and Privacy Act (FERPA) within a consortial environment. FERPA requirements were examined, as well as college and library policy and procedure. It was determined that information in library patron records is directory information and, under most circumstances, does not need FERPA protections. However, the needs of the confidential student, who requests confidentiality of all information, including directory information, were identified as not having been addressed. Reed Library adjusted policy and procedures to meet the needs of the confidential student and fulfill FERPA requirements.